1991
DOI: 10.1111/j.1476-5381.1991.tb09819.x
|View full text |Cite
|
Sign up to set email alerts
|

Time‐dependent synergistic interactions between the vasodilator neuropeptide, calcitonin gene‐related peptide (CGRP) and mediators of inflammation

Abstract: 1 The action of the long lasting neuropeptide vasodilator, calcitonin gene-related peptide (CGRP), in potentiating oedema formation and neutrophil accumulation was investigated in the dorsal skin of the rabbit, in vivo. Combinations of agents under test were administered by intradermal (i.d.) injection. Oedema formation and neutrophil accumulation were then measured by quantitative radiolabel techniques.2 CGRP (1 x 10-1 mol per site) potentiated neutrophil accumulation induced by zymosan activated plasma, (use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
2

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 26 publications
1
30
2
Order By: Relevance
“…A new and relevant finding of the present study are the results showing that as reported previously for BK-mediated increase in paw volume and BKinduced increase of vascular permeability (Brain & Williams, 1989;Buckley et al, 1991;Cruwys et al, 1992), the B1 receptor agonist, DABK, can also interact synergistically with several inflammatory mediators following systemic treatment with LPS. This view is substantiated by the results showing that coinjection of very low doses of PGE2, PGI2, SP, CGRP, PAF or 5-HT (each 1 nmol), when injected alone caused little or no oedema formation, but induced a pronounced potentiation of DABK-induced increase in paw volume.…”
Section: Discussionsupporting
confidence: 83%
“…A new and relevant finding of the present study are the results showing that as reported previously for BK-mediated increase in paw volume and BKinduced increase of vascular permeability (Brain & Williams, 1989;Buckley et al, 1991;Cruwys et al, 1992), the B1 receptor agonist, DABK, can also interact synergistically with several inflammatory mediators following systemic treatment with LPS. This view is substantiated by the results showing that coinjection of very low doses of PGE2, PGI2, SP, CGRP, PAF or 5-HT (each 1 nmol), when injected alone caused little or no oedema formation, but induced a pronounced potentiation of DABK-induced increase in paw volume.…”
Section: Discussionsupporting
confidence: 83%
“…Several studies have suggested a pro-inflammatory activity for CGRP (Gamse & Saria, 1985;Buckley et al, 1991;1992). However, in our model CGRP837 was unable to inhibit the TDI-induced tracheal hyperreactivity and the cutaneous responses.…”
Section: Discussioncontrasting
confidence: 69%
“…The tachykinins have been shown to induce proliferation of mitogenstimulated T-lymphocytes (Payan et al, 1983;Stanisz et al, 1986;Casini et al, 1989), migration of leukocytes (Marasco et al, 1981;Moore, 1984), and activation of macrophages (Koff & Dunegan, 1985). In contrast, CGRP has been found to inhibit the proliferation of mitogen-stimulated T-lymphocytes (Umeda et al, 1988;Casini et al, 1989), although several studies also suggest that CGRP may be pro-inflammatory on its own (Gamse & Saria, 1985;Buckley et al, 1991;1992). In the literature the role for sensory neuropeptides in the induction of airway hyperreactivity has been investigated in several studies (Boichot et al, 1995;Sakamoto et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, kinins may also stimulate visceral sensory neurones to release pro-inflammatory neuropeptides such as substance P (SP), neurokinin A or calcitonin gene-relatedpeptide (CGRP) (Bhoola et al, 1992; for review see: Farmer & Burch, 1992;Geppetti, 1993). Therefore, a large part of the pro-inflammatory and algesic actions of kinins is most likely to be due to synergistic actions between these mediators (Brain & Williams, 1989;Buckley et al, 1991;Cruwys et al, 1992;Warren et al, 1993).…”
Section: Introductionmentioning
confidence: 99%